2022
DOI: 10.3390/s22155717
|View full text |Cite
|
Sign up to set email alerts
|

Sea Cucumber Detection Algorithm Based on Deep Learning

Abstract: The traditional single-shot multiBox detector (SSD) for the recognition process in sea cucumbers has problems, such as an insufficient expression of features, heavy computation, and difficulty in application to embedded platforms. To solve these problems, we proposed an improved algorithm for sea cucumber detection based on the traditional SSD algorithm. MobileNetv1 is selected as the backbone of the SSD algorithm. We increase the feature receptive field by receptive field block (RFB) to increase feature detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The P-R curve can be used to reflect the performance of the model. The improved YOLOv7-GDAW model has a larger area enclosed by the two coordinate axes of the P-R curve 40 , and its Break-Even Point is closer to the coordinate point (1,1). Based on these comparisons, it can be shown that the improved ship detection model YOLOv7-GDAW system performs better.…”
Section: Validation Of the Improved Yolov7 Modelmentioning
confidence: 89%
“…The P-R curve can be used to reflect the performance of the model. The improved YOLOv7-GDAW model has a larger area enclosed by the two coordinate axes of the P-R curve 40 , and its Break-Even Point is closer to the coordinate point (1,1). Based on these comparisons, it can be shown that the improved ship detection model YOLOv7-GDAW system performs better.…”
Section: Validation Of the Improved Yolov7 Modelmentioning
confidence: 89%
“…Li et al [33] added an extra detection head to the YOLOv5 model to improve multi-scale detection and small target detection accuracy. Zhang et al [34] combined an attention mechanism to learn target features and increase the receptive field to improve the detection accuracy and robustness of underwater small target detection. Yao et al [35,36] used residual networks as a backbone network to improve the efficiency of sea cucumber feature extraction.…”
Section: Introductionmentioning
confidence: 99%
“…Giving an additional detection head to the YOLOv5 model could also enhance the multiple scale detection and improve the detection accuracy of small targets [ 17 ]. Attention mechanisms were effective in learning object features and increasing the receptive field could improve the detection accuracy and robustness in recognizing underwater small targets [ 18 ]. Furthermore, many works were reported on the modification of feature extraction networks which improved the ability of the feature representation of underwater targets.…”
Section: Introductionmentioning
confidence: 99%